The impact of the Islamic Community processes on Bosniak Emigration through the analysis of the journal „Bosanski pogledi” - Hamza Memišević (Historijski pogledi)
The paper analyzes the role of the journal „Bosanski pogledi” in the context of the processes within the Islamic Community (IVZ) during the 1960s, a period when Reis-ul-Ulema Sulejman ef. Kemura led this religious institution. He was referred to as the “red reis” by defeated circles both within and outside of Yugoslavia. The ahistorical label “red” served to indicate the proximity of Reis-ul-Ulema Kemura and by extension, the Islamic Community to the Yugoslav state leadership. With the establishment of the Democratic Federative Yugoslavia (from 1946, FNRJ), Bosnian-Herzegovinian Muslims experienced a profound political and national transformation. Real and potential opponents of the regime were removed from political life, and cultural and religious institutions faced a similar fate. Yugoslav communism sought to eliminate autonomy and any distinctiveness in relation to the state. The preservation of complete autonomy and distinctiveness concerning the state apparatus after World War II appeared to be an unattainable goal, given the nature of communist ideology. During this period, the Islamic Community found itself in a precarious situation. The staff and infrastructural disintegration resulting from World War II accelerated the process of the state apparatus gaining control over this institution. The unfavorable financial situation of the Islamic Community and its officials was cleverly exploited by the state through a carrot-and-stick approach. Within the Islamic Community, a group of religious officials emerged who represented the interests of the state, and thus those of the Islamic Community. Discontent with the developments, defeated circles of Bosnian-Herzegovinian Muslims, who escaped death during the revolutionary upheaval and continued their national-political mission abroad, expressed critical views towards the newly established leadership of the Islamic Community. This politically negative stance towards the leadership represented actors from the political life of the Independent State of Croatia. Initially, the criticism of the Islamic Community’s leadership came from Muslims who identified as Croats, with the ultimate goal of reinstating the Croatian state. The later emergence of Bosniak emigration, initiated by Adil Zulfikarpašić, adopted the principle of criticizing the Islamic Community as reflected in „Bosanski pogledi”, but did not seek the dismantling of Yugoslavia. „Bosanski pogledi” systematically reported on events within the Islamic Community, violations of religious freedoms, and the interference of the state leadership in the institution’s operations. During the years when „Bosanski pogledi” was published, contacts were reactivated with emigration, involving individuals from the interwar and wartime periods of Muslim civic politics who had previously been sentenced by communist courts. The editorial board of „Bosanski pogledi” obtained sensitive materials through dissatisfied individuals in the homeland, which were later published in the journal, alongside elaborations on the difficult position of the central religious institution of Yugoslav Muslims. To achieve a comprehensive understanding of this topic, it is necessary to analyze several components, including the conditions within the Islamic Community before the emergence of „Bosanski pogledi” and the situation among Bosnian-Herzegovinian Muslims in emigration. A significant question arises: was the initial orientation of Bosnian-Herzegovinian Muslims towards Serbian or Croatian emigration a historical reality or a necessity? The research subject spans the period from 1945 to 1967, when the last issue of „Bosanski pogledi” in emigration was published.